A Review of Contact Electrification at Diversified Interfaces and Related Applications on Triboelectric Nanogenerator - Hu, Jun; Iwamoto, Mitsumasa; Chen, Xiangyu (Nano-Micro Letters, 2023)
The triboelectric nanogenerator (TENG) can effectively collect energy based on contact electrification (CE) at diverse interfaces, including solid–solid, liquid–solid, liquid–liquid, gas–solid, and gas–liquid. This enables energy harvesting from sources such as water, wind, and sound. In this review, we provide an overview of the coexistence of electron and ion transfer in the CE process. We elucidate the diverse dominant mechanisms observed at different interfaces and emphasize the interconnectedness and complementary nature of interface studies. The review also offers a comprehensive summary of the factors influencing charge transfer and the advancements in interfacial modification techniques. Additionally, we highlight the wide range of applications stemming from the distinctive characteristics of charge transfer at various interfaces. Finally, this review elucidates the future opportunities and challenges that interface CE may encounter. We anticipate that this review can offer valuable insights for future research on interface CE and facilitate the continued development and industrialization of TENG. Highlights: 1 The distinctive characteristics, underlying mechanisms, diverse range of selected materials, and modification methods of contact electrification (CE) at various interfaces are summarized and comparatively analyzed, offering valuable guidance for future investigations of triboelectric nanogenerator (TENG) at different interfaces. 2 This review gives a detailed insight into the unique applications of TENG relying on different interfacial electrification. 3 The challenges and development prospects of TENGs based on CE are discussed.